Unscheduled Healthcare Contact after Outpatient Surgical Fixation of Distal Radius Fractures: A Retrospective Cohort Study - Ambika Menon, BS; Samuel H. Payne, MD; Evan D. Woodard, BS; Rachel E. Williams, BA; Jesse I. Emefiele, BS; William J. Knaus, MD; Paul A. Ghareeb, MD (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. Distal radius fractures (DRFs) commonly require surgical fixation. Unscheduled healthcare contact (UHC) after surgery represents an area of quality improvement in surgical care. We hypothesize that UHC after outpatient surgical fixation of DRFs is more common in patients undergoing treatment at a safety-net hospital versus those treated at a university-affiliated facility. Methods:. An IRB-approved retrospective review studied patients who underwent outpatient surgical treatment of DRFs from January 2017 to May 2021. Surgery was performed either at a local safety-net hospital or at a university-affiliated hospital. UHC was defined as telephone calls, emergency room visits, and/or readmissions to the hospital within 30 days of surgery. Demographic factors, medical comorbidities, and injury and surgery details were analyzed. Results:. In total, 442 patients met inclusion criteria. An estimated 257 patients (58.1%) were treated at a university-affiliated facility, whereas 185 patients (41.9%) had surgery at the safety-net hospital. The overall rate of UHC within thirty-days of surgery was 14.0%, with the most common reason being uncontrolled pain. Rates of UHC were higher at the safety-net hospital compared with those at a university-affiliated facility (26.5% versus 5.1%, P < 0.05). Conclusions:. UHC was significantly greater for patients undergoing surgery in a safety-net hospital setting compared with those in a university setting. UHC after surgery is often related to inadequate postoperative pain control. Improved pain control and patient education may alleviate unnecessary healthcare contact.